The Global Music Therapy Educators Network. (November 2020) - McCaffrey, Tríona; McFerran, Katrina; Gattino, Gustavo; Sundar, Sumathy
Music therapy educators around the globe are united in their commitment to the development of the profession through the education of new professionals. Although different university programmes emphasise diverse approaches and are representative of their surrounding cultures, there is much that is shared between different programmes and educators. However, prior to the COVID-19 pandemic, there was minimal interaction between educators as a group, possibly due to time pressures and a lack of need to unite and celebrate our diversities. With the onset of the pandemic and the rapid transition to online learning, an unexpected space emerged for collective dialogue among the music therapy educator community. Brought together by the challenges imposed on professional training due to a global pandemic, a number of global educators united in discussion to seek a way forward.